The influence of financial literacy, self-efficacy, and lifestyle on financial management behavior - Viacenza, Viacenza (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
The management of finances represents a significant challenge in the lives of students, influenced by various factors. Consequently, this research seeks to explore and analyze the interplay between financial literacy, self-efficacy, and lifestyle in relation to financial management behaviors, while also considering locus of control as a mediating variable. The study focuses on students enrolled in the Faculty of Economics and Business at the University of Bandar Lampung. A random sampling method was employed, utilizing Slovin's formula for sample size determination. Data analysis was conducted using Smart-PLS version 4.1.0.3, applying the Structural Equation Modeling-Partial Least Square (SEM-PLS) technique. A total of 128 student respondents were successfully surveyed. The results of the research reveal a significant impact of financial literacy, self-efficacy, and lifestyle on financial management behaviors; however, the mediating variable did not demonstrate a significant effect on the dependent variable.